Development and Evaluation of an AI-Powered E-Module for Microsoft Excel Instruction in Indonesian Vocational Schools - Eva Faradila Sandi; Sutirman Sutirman (AL-ISHLAH: Jurnal Pendidikan, 2025)
As digital competence becomes essential in the modern workplace, vocational students must master tools like Microsoft Excel. However, traditional instruction in Indonesian vocational schools often lacks adaptability and interactivity. This study aimed to develop and evaluate an AI-powered e-module to enhance students’ Excel skills through adaptive learning. Using the ADDIE development model, an AI-integrated e-module was designed and implemented in four vocational schools across Yogyakarta, Central Java, and West Java. The study involved 144 students from the Office Management and Business Services program, divided into experimental and control groups. Data were collected through expert validation, pre- and post-tests, usability questionnaires, and observations. Quantitative analysis included t-tests, N-Gain calculation, and validation of reliability using Cronbach’s Alpha. Expert evaluations rated the module as highly feasible (scores ≥85%). Students in the experimental group showed significantly greater learning gains (N-Gain = 0.65, medium-high category) compared to the control group (N-Gain = 0.42). T-test results confirmed a significant difference (t(142) = 4.72, p .001, d = 0.78). Students also reported improved motivation, confidence, and learning autonomy, while teachers observed reduced need for procedural guidance. The findings demonstrate that AI-powered modules can significantly enhance technical skills in vocational education by offering personalized feedback and adaptive content. The module supports self-directed learning and aligns with the Merdeka Belajar initiative. This study contributes a scalable instructional model for integrating AI into skill-based learning environments.